Predicting re-incarceration status of prisoners in contemporary China: Applying Western Criminological Theories - Messner, Steven F. (International journal of offender therapy and comparative criminology, 2018)
Studies have revealed that self-control theory, social learning theory, and strain theory are useful in explaining criminal activity in China. Previous research with Chinese data, however, has focused almost exclusively on samples of adolescents and the minor types of offending that are typically captured in such samples. The present study builds upon prior work by considering the extent to which these three major etiological theories of crime can help differentiate between profiles of Chinese prisoners categorized with respect to re-incarceration status. Specifically, we derive hypotheses that predict prisoners’ status as first-time inmates or inmates with multiple incarcerations. These hypotheses are assessed with recently collected data for a sample of approximately 1,800 prisoners in Southern China. The results reveal that indicators of peer criminality, low self-control, and negative emotions (a theorized outcome of experiences of strain) are all positively associated with re-incarceration status.